Factors affecting the effectiveness of road transpot system in Kota Bharu - Chong, Jia Yin; Suib, Erna Lyana; R. Veerasingam, Gauslya; Sarapah, Herdawati (2015)
This research objective is to study the factor affecting the effectiveness of road transport system in Kota Bharu, Kelantan. The effectiveness of road transport system in KOta Bharu will affect by road condition, road signage road network and road quality. Survey data was distributed and answered by the Kota Bharu residents who are able to drive. There are total 400 data smapling questionnaires were collected for this research. This research has shown the hypothesized linkage between each of the road factor and road transport system was significantly supported. Lastly , limitations and recommendation have discussed in this research.